Investigation of supply chain flexibility using a forced field analysis – a case study. (1st January 2012) - More, Dileep; Subash Babu, A.
Today's supply chains are operating in complex, risky, ambiguous and uncertain business environments. Managers of supply chain (SC) are therefore under pressure to build high level of flexibility in the SC operations. However, supply chain flexibility (SCF) is a complex, dynamic, multifaceted, context specific and application-oriented concept, viewed from a strategic and customer perspective. SCF is not easy to comprehend and put into real practice, the foremost reason is the diverse nature of the three forces viz. stimuli, enablers and inhibitors and their dynamics in the SC. In this paper, an attempt has been made to investigate SCF from a company perspective, especially in the viewpoint of making SCF a reality. The relevant data collected from the organisation is used to analyse the dynamics among the three forces using force field analysis (FFA). The study appears to be promising in the point of view of developing a decision support system for managing SCF.